Studi Komparasi Metode Pengajaran di Sekolah Dasar Indonesia dan Sekolah Dasar Thailand - Stefanie Marla Laudia; Ari Metalin Ika Puspita; Neni Mariana (Journal on Education, 2023)
This study compares teaching methods in Indonesian and Thai elementary schools using a descriptive comparative approach. The results show that there are significant differences in government support for education in the two countries. Thailand has significantly greater government support, which is reflected in the provision of well-equipped school facilities, including technology. These facilities allow teachers to use more interactive teaching methods. On the other hand, Indonesia has more limited government support. However, Indonesia has developed a strategy that emphasizes inclusivity and community empowerment. This strategy is reflected in the curriculum, teaching methods, and evaluation approaches. Despite these differences, both countries share a commitment to improving the quality of education. The study highlights the importance of understanding the social, cultural, and policy context when designing effective teaching methods. By adopting best practices from each other, governments and educators can enhance elementary-level learning.